Intramolecular hydrogen abstraction in radicals derived from inositol 1,3-acetals: efficient access to cyclitols - Murali, Chebrolu; Gurale, Bharat P.; Shashidhar, Mysore S. (European Journal of Organic Chemistry, 2010)
The benzylidene acetals obtained by cleavage of the orthobenzoate moiety in myo-mositol 1,3,5-orthobenzoate were used to prepare mono- as well as di-deoxy inositol derivatives via their xanthates. The dideoxygenation is a result of intramolecular abstraction of the benzylidene acetal hydrogen and subsequent cleavage of the acetal ring. Such a cleavage does not take place in analogous acetals derived from other orthoesters. The 1,3-acetals derived from myoinositol 1,3,5-orthoesters were also used to prepare neo-inositol and isomeric deoxy-amino inositols, Most of the reactions in these synthetic sequences starting from myo-inositol give one product in each step. The results presented here show that myo-inositol 1,3,5-orthobenzoate offers many advantages over other orthoesters for the synthesis of cyclitol derivatives from myo-inositol.
Keywords: cyclitols; Deoxygenation; Inosamine; Inositol; Radical reactions; Radicals; Xanthate

Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate